A systematic review of mental health literacy in Pakistan - Munawar, Khadeeja; Abdul Khaiyom, Jamilah Hanum; Bokharey, Iram Zehra; Sang-Ah Park, Miriam; Riaz, Fahad (John Wiley & Sons Australia, Ltd, 2020)
Individual mental health has become a primary global concern. In Pakistan, the prevalence of mental health issues is still unclear, as not many studies have assessed the level of mental health literacy (MHL) in the country. This systematic review aims to bridge this gap by encouraging the early detection of mental disorders, lessening stigma, and improving help-seeking behavior. Nine electronic databases were searched to identify empirical literature in this area. Only studies that evaluated MHL efficacy and those published in English were selected. Non-peer reviewed articles and gray literature were excluded. From 613 studies retrieved, 59 studies met the inclusion criteria and were reviewed. Forty-three of the included studies mentioned mental health outcome measures (of which only four mentioned reliability indices), 13 discussed stigma, 18 examined help-seeking approaches to mental illness treatments, and 47 discussed mental health knowledge. Additionally, the outcome of the MHL measures had considerable heterogeneity and limited validity. Meta-analysis was not conducted due to a lack of MHL operationalization